2006
DOI: 10.1021/bi052606b
|View full text |Cite
|
Sign up to set email alerts
|

Active-Site Assembly in Glutaminyl-tRNA Synthetase by tRNA-Mediated Induced Fit

Abstract: Structure-based mutational analysis was employed to probe an unusual intramolecular interaction between partially buried glutamate residues adjacent to the active site of Escherichia coli glutaminyltRNA synthetase (GlnRS). Crystal structures of unliganded GlnRS and of the GlnRS-tRNA Gln complex reveal that the Glu34 and Glu73 side-chain carboxylates contact each other only in the tRNA-bound state, and that the interaction is formed via mutual induced-fit transitions that occur en route to the ground-state Mich… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 23 publications
0
20
0
Order By: Relevance
“…The reaction is most likely substrate assisted, with the phosphate of the adenylate acting as the general base to abstract the proton from the 2′OH in a concerted mechanism 14,36 (Fig. 4c).…”
Section: Resultsmentioning
confidence: 99%
“…The reaction is most likely substrate assisted, with the phosphate of the adenylate acting as the general base to abstract the proton from the 2′OH in a concerted mechanism 14,36 (Fig. 4c).…”
Section: Resultsmentioning
confidence: 99%
“…For glutamyl-tRNA synthetase, the presence of tRNA eliminates non-specific binding of d-glutamic acid and l-aspartic acid to the enzyme [9,10]. Detailed analysis of glutaminyl-tRNA synthetase has led to the proposal of an induced-fit type of active site rearrangement that plays a role in enzyme specificity [11][12][13], and the concept of discriminatory elements in tRNA that participate in amino acid selection has been proposed [14]. It would then be consistent with our observations for jack bean tRNA Arg to trigger an active site rearrangement in the jack bean enzyme that provides the means to enhance amino acid discrimination.…”
Section: Discussionmentioning
confidence: 99%
“…For others that are specific for structurally idiosyncratic amino acids, no active editing may be required. In the case of glutamyl‐ and glutaminyl‐tRNA synthetases, which together with arginyl‐tRNA synthetase form a subgroup of enzymes that require tRNA for amino acid activation, the potential for misrecognition of related amino acids has been investigated [9–13] and modulated by amino acid replacements and active site redesign [14]. A mechanism that does not rely on hydrolytic editing but resembles an induced fit type of substrate selection, including the participation of tRNA structural features, has been proposed [14].…”
mentioning
confidence: 99%
“…16 Based on their observed dissimilar active sites and apparent common utilization of a non-bridging phospho-oxygen of the substrate as the mechanistic base, it has been suggested that for aaRS's such a substrate-assisted catalysis (SAC) mechanism may be a general feature of these presumably ancient enzymes. 5,16,2226 …”
Section: Introductionmentioning
confidence: 99%